Blocking ATM-dependent NF-κB pathway overcomes niche protection and improves chemotherapy response in acute lymphoblastic leukemia - Chen, Ya-Li; Tang, Chao; Zhang, Meng-Yi; Huang, Wen-Li; Xu, Yan; Sun, Hui-Yin; Yang, Fan; Song, Li-Li; Wang, He; Mu, Li-Li; Li, Ming-Hao; Zheng, Wei-Wei; et al. (Leukemia, 2019)
Bone marrow (BM) niche responds to chemotherapy-induced cytokines secreted from acute lymphoblastic leukemia (ALL) cells and protects the residual cells from chemotherapeutics in vivo. However, the underlying molecular mechanisms for the induction of cytokines by chemotherapy remain unknown. Here, we found that chemotherapeutic drugs (e.g., Ara-C, DNR, 6-MP) induced the expression of niche-protecting cytokines (GDF15, CCL3 and CCL4) in both ALL cell lines and primary cells in vitro. The ATM and NF-κB pathways were activated after chemotherapy treatment, and the pharmacological or genetic inhibition of these pathways significantly reversed the cytokine upregulation. Besides, chemotherapy-induced NF-κB activation was dependent on ATM-TRAF6 signaling, and NF-κB transcription factor p65 directly regulated the cytokines expression. Furthermore, we found that both pharmacological and genetic perturbation of ATM and p65 significantly decreased the residual ALL cells after Ara-C treatment in ALL xenograft mouse models. Together, these results demonstrated that ATM-dependent NF-κB activation mediated the cytokines induction by chemotherapy and ALL resistance to chemotherapeutics. Inhibition of ATM-dependent NF-κB pathway can sensitize ALL to chemotherapeutics, providing a new strategy to eradicate residual chemo-resistant ALL cells.